14-3-3 Proteins in Glutamatergic Synapses. (23rd April 2018) - Zhang, Jiajing; Zhou, Yi
Abstract : The 14-3-3 proteins are a family of proteins that are highly expressed in the brain and particularly enriched at synapses. Evidence accumulated in the last two decades has implicated 14-3-3 proteins as an important regulator of synaptic transmission and plasticity. Here, we will review previous and more recent research that has helped us understand the roles of 14-3-3 proteins at glutamatergic synapses. A key challenge for the future is to delineate the 14-3-3-dependent molecular pathways involved in regulating synaptic functions.